2017
DOI: 10.1155/2017/3540756
|View full text |Cite
|
Sign up to set email alerts
|

Yogi Detox Tea: A Potential Cause of Acute Liver Failure

Abstract: We present a case of acute fulminant liver failure from a liver detoxification tea. We present a 60-year-old female with weakness, lethargy, scleral icterus, jaundice, and worsening mental status. She drank herbal tea three times a day for 14 days prior to symptom development. Liver tests were elevated. Remaining laboratory tests and imaging were negative for other etiologies. An ultrasound-guided liver biopsy showed submassive necrosis. A literature search on the ingredients shows six ingredients as having he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…With 11,609 the largest HILI case number was published in 2019 ( Figure 3 ) as a consequence of the ongoing worldwide use of RUCAM for assessing causality in suspected HILI cases ( Table 4 ). In particular, contributing countries were in alphabetical order Australia [ 29 ], Brazil [ 183 ], China [ 48 , 196 , 197 , 198 , 199 , 200 , 201 ], Germany [ 213 , 214 , 215 ], India [ 217 ], Italy [ 222 ], Korea [ 103 ], Spain [ 115 , 117 , 240 , 241 , 242 ], Switzerland [ 244 ], and the US [ 245 , 246 , 247 , 248 , 249 , 250 , 251 , 252 , 253 , 254 ]. Most of the 11,619 HILI cases published in 2019 were from China [ 48 , 196 ] and Korea [ 103 ], with 6971 cases published by Shen et al [ 48 ], 2019 cases reported by Byeon et al [ 103 ], and 1552 cases provided by Chow et al [ 196 ].…”
Section: Worldwide Publications Of Hili Cases Assessed For Causalimentioning
confidence: 99%
“…With 11,609 the largest HILI case number was published in 2019 ( Figure 3 ) as a consequence of the ongoing worldwide use of RUCAM for assessing causality in suspected HILI cases ( Table 4 ). In particular, contributing countries were in alphabetical order Australia [ 29 ], Brazil [ 183 ], China [ 48 , 196 , 197 , 198 , 199 , 200 , 201 ], Germany [ 213 , 214 , 215 ], India [ 217 ], Italy [ 222 ], Korea [ 103 ], Spain [ 115 , 117 , 240 , 241 , 242 ], Switzerland [ 244 ], and the US [ 245 , 246 , 247 , 248 , 249 , 250 , 251 , 252 , 253 , 254 ]. Most of the 11,619 HILI cases published in 2019 were from China [ 48 , 196 ] and Korea [ 103 ], with 6971 cases published by Shen et al [ 48 ], 2019 cases reported by Byeon et al [ 103 ], and 1552 cases provided by Chow et al [ 196 ].…”
Section: Worldwide Publications Of Hili Cases Assessed For Causalimentioning
confidence: 99%
“…The administration of the three different concoctions neither caused any observable changes in the histology of the liver, kidney and intestine nor in the biochemical parameters of the liver and kidney functions of the treated animals. Analysis of diagnostic serum parameters for liver functions (ALT and AST) and kidney functions (Creatinine) showed that the values were within normal range even at high doses, and whereas toxicities of substances are manifested as liver and kidney irregularities due to the involvement of these organs with metabolism [17,18,19]. In this study, no significant difference was observed in the levels of serum biochemical parameters in the treated animals and likewise no changes were seen on histological examination.…”
Section: Discussionmentioning
confidence: 40%
“…Finally, laboratory testing indicated liver injury, which represents another potential cause of hyponatremia. Although this mechanism is unlikely in this case, it is a worthy consideration given that complementary and alternative medicine products have previously been associated with acute liver failure [5,6].…”
Section: Discussionmentioning
confidence: 88%
“…Consequently, their effectiveness and adverse effects are understudied, despite plausibly having the potential to detrimentally affect health outcomes. Previous reports suggest that complementary and alternative medicine products may cause acute liver failure [5,6].…”
Section: Introductionmentioning
confidence: 99%